Enhanced electrochemical performance of Li-rich cathode materials through microstructural control. Issue 35 (31st August 2018) - Serrano-Sevillano, Jon; Reynaud, Marine; Saracibar, Amaia; Altantzis, Thomas; Bals, Sara; van Tendeloo, Gustaaf; Casas-Cabanas, Montse
Abstract : Structural defects are used as a design opportunity to prepare better battery materials: limiting capacity and voltage fadings in Li2 MnO3 . Abstract : The microstructural complexity of Li-rich cathode materials has so far hampered understanding the critical link between size, morphology and structural defects with both capacity and voltage fadings that this family of materials exhibits. Li2 MnO3 is used here as a model material to extract reliable structure–property relationships that can be further exploited for the development of high-performing and long-lasting Li-rich oxides. A series of samples with microstructural variability have been prepared and thoroughly characterized using the FAULTS software, which allows quantification of planar defects and extraction of average crystallite sizes. Together with transmission electron microscopy (TEM) and density functional theory (DFT) results, the successful application of FAULTS analysis to Li2 MnO3 has allowed rationalizing the synthesis conditions and identifying the individual impact of concurrent microstructural features on both voltage and capacity fadings, a necessary step for the development of high-capacity Li-ion cathode materials with enhanced cycle life.